Comparison between Two Different Feed Formulations to Ensure the Growth of Young Pigeon Squabs - Mahaboobjan, S.; Rajakumari, D. V. Sheeba; Dilda , I. Jenci; Esakkiammal, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Background: Feed formulation plays a vital role in squabs of racing pigeon’s growth and preparing them for the race from its young age. Some feed formulations which have more protein and fat content has the ability to improve the weight of the eggs and young squabs. Objective: In this study, two different feed formulations were compared for the parent pigeons for its antenatal and postnatal period to ensure which is suitable and enhance the growth of the eggs and young squabs. Methods: Two pairs of racing pigeons Pair A and Pair B have been selected. They fed with two types of feed formulations like one with a basic nutrients and another one with an addition of protein and lipid content. The weight of the eggs and the squabs of these pigeons have been measured. Results: The average weight of eggs in Pair B (19.16g) is higher than the Average weight of eggs in Pair A (16.75g). At the end of 20thday it was observed that the average weight of the squabs in Pair B (260.41g) is higher than the average weight of squabs in Pair A (229.59g). Conclusion: The result showed that there is a significant weight difference in the eggs and squabs of pair A and pair B. This difference occurs due to the addition of some nutritious feed ingredients in the feed prepared for the Pair B pigeons.